Technological chance and growth regimes: Assessing the case for universal basic income in an era declining labour shares - Joe Chrisp; Aida Garcia-Lazaro; Nick Pearce (Albert-Ludwigs-Universität Freiburg, Freiburg Institute for Basic Income Studies (FRIBIS), 2023)
[Synopsis and motivation] In recent decades, most OECD countries have seen a significant decline in the labour share, as well as an increase in inequality. The decline in the labour share and the rise in inequality poses several problems for such countries, whether related to distributive justice, economic and social outcomes, such as deficient aggregate income and demand, or democratic politics. In this report, we focus on the role of technological change as a central driver of the decline in the labour share and explore its contingency: both across contexts and across definitions/operationalisations of technology. With respect to the latter, we distinguish between perspectives that place physical capital and investment in automation and ICT at the centre of technological change on the one hand, and the growth of the knowledge economy and intangible capital on the other. Meanwhile, following work by Baccaro and Pontusson (2016), and more recently Hassel and Palier (2021), we utilise the concept of 'growth regimes' to analyse how the effects of technology are mediated and moderated by national political-economic institutions. This approach allows us to test more nuanced arguments about the role of technological change in the decline in the labour share and to discuss the likely effects, and political feasibility, of policy solutions such as universal basic income (UBI) that are often advanced as an answer to increased automation and lower returns to labour. The following issues provide the basis for our research questions: 1. To what extent is technological change responsible for the decline in the labour share? 2. What is the role of growth regimes in moderating the effect of technology on the labour share? 3. Are results consistent across different conceptions and definitions of technological change? 4. What policy solutions are available to tackle these trends and issues? 5. Does technological change strengthen the case for and the feasibility of a universal basic income? This work builds on previous policy briefs and reports by the Institute for Policy Research (IPR) on UBI and technological change, namely the September 2019 report by Dr Luke Martinelli entitled 'Basic income, automation and labour market change' (Martinelli, 2019a). That report summarised the evidence regarding the effects of technology on labour markets and the case for UBI in such a light. Empirical analysis, however, focused on political economy questions concerning the political constituency for a UBI and policy trade-offs in design across EU countries using microsimulation analysis. Here, our empirical strategy is instead focused on questions about the effect of technology on the labour share, enabling us to re-pose the question of how a UBI could serve as a tool for combating growing inequality, income and demand deficiency, and labour market dysfunction in global economies. Future empirical research at the IPR will focus more comprehensively on the fifth and final research question above, namely estimating the macroeconomic effects of a UBI, including one funded using sovereign money. Next, we introduce three central ideas in the report - the decline in the labour share, technological change and growth regimes - before briefly outlining the consequences for policy debates.
Keywords: 330; Technischer Fortschritt; Lohnquote; Grundeinkommen; Theorie